Epigenetic and Transcriptome Profiling Identifies a Population of Visceral Adipose-Derived Progenitor Cells with the Potential to Differentiate into an Endocrine Pancreatic Lineage. Issue 1 (January 2019) - Williams, Michael D.; Joglekar, Mugdha V.; Satoor, Sarang N.; Wong, Wilson; Keramidaris, Effie; Rixon, Amanda; O'Connell, Philip; Hawthorne, Wayne J.; Mitchell, Geraldine M.; Hardikar, Anandwardhan A.
Type 1 diabetes (T1D) is characterized by the loss of insulin-producing β-cells in the pancreas. T1D can be treated using cadaveric islet transplantation, but this therapy is severely limited by a lack of pancreas donors. To develop an alternative cell source for transplantation therapy, we carried out the epigenetic characterization in nine different adult mouse tissues and identified visceral adipose-derived progenitors as a candidate cell population. Chromatin conformation, assessed using chromatin immunoprecipitation (ChIP) sequencing and validated by ChIP-polymerase chain reaction (PCR) at key endocrine pancreatic gene promoters, revealed similarities between visceral fat and endocrine pancreas. Multiple techniques involving quantitative PCR, in-situ PCR, confocal microscopy, and flow cytometry confirmed the presence of measurable (2–1000-fold over detectable limits) pancreatic gene transcripts and mesenchymal progenitor cell markers (CD73, CD90 and CD105; >98%) in visceral adipose tissue-derived mesenchymal cells (AMCs). The differentiation potential of AMCs was explored in transgenic reporter mice expressing green fluorescent protein (GFP) under the regulation of the Pdx1 (pancreatic and duodenal homeobox-1) gene promoter. GFP expression was measured as an index of Pdx1 promoter activity to optimize culture conditions for endocrine pancreatic differentiation. Differentiated AMCs demonstrated their capacity to induce pancreatic endocrine genes as evidenced by increased GFP expression and validated using TaqMan real-time PCR (at least 2–200-fold relative to undifferentiated AMCs). Human AMCs differentiated using optimized protocols continued to produce insulin following transplantation in NOD/SCID mice. Our studies provide a systematic analysis of potential islet progenitor populations using genome-wide profiling studies and characterize visceral adipose-derived cells for replacement therapy in diabetes.